INFLASI, UPAH DAN PENGANGGURAN DI KABUPATEN MAJALENGKA (PENDEKATAN ERROR CORRECTION MODEL) - L Suparto LM; Pipih Sopiyan (Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this research is to look at the short-term and long-term impacts of inflation and wages on unemployment in Majalengka Regency. The subjects of this research analysis are inflation, wages, and unemployment in Majalengka Regency from 2008 to 2022, this study employs a quantitative approach, meaning the use of numbers. Secondary data were acquired from archives issued by the West Java Province and Majalengka Regency's Central Bureau of Statistics. The Domowitz-El Badawi error correction model was employed in the analysis. According to the findings, inflation has a positive impact on unemployment in the near term but a negative and significant impact on it in the long run. This suggests that inflation remains a concern for the economy, particularly in the short term. The impact of wages on unemployment is negative and considerable both in the short and long terms. This indicates that too high wages may cause the demand for work  decline, which would increase unemployment. To keep wages at a level that balances the supply and demand for labor, a collective agreement is thus required between workers, the government, and businesses. This will assist to reduce the long-term detrimental effects of inflation and wages on unemployment.